2020
DOI: 10.1016/j.hpb.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Arterial resections in pancreatic cancer – Systematic review and meta-analysis

Abstract: Background: The number of pancreatic resections due to cancers is increasing. While concomitant venous resections are routinely performed in specialized centers, arterial resections are still controversial.Nevertheless they are performed in patients presenting with locally advanced tumors. Our aim was to summarize currently available literature comparing peri-operative and long-term outcomes of arterial and non-arterial pancreatic resections. Methods:We included studies comparing pancreatic operations with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 47 publications
1
21
0
5
Order By: Relevance
“…In our series, a patient who underwent sub-adventitial divestment developed a hepatic artery pseudoaneurysm whose bleeding was controlled by interventional radiology. Nevertheless, studies have shown that the divestment technique is safe and without excessive mortality, especially when compared to arterial resection and reconstruction [ 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our series, a patient who underwent sub-adventitial divestment developed a hepatic artery pseudoaneurysm whose bleeding was controlled by interventional radiology. Nevertheless, studies have shown that the divestment technique is safe and without excessive mortality, especially when compared to arterial resection and reconstruction [ 16 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, almost all surgeons in this study would declare a tumour unresectable intraoperatively if arterial involvement were identified, particularly of the superior mesenteric artery. Arterial resection and reconstruction in PDAC have been previously reported in very selective cases ( 43 ), but is characterised by high rates of postoperative complications and questionable survival benefit ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…This literature review will provide an overview on current evidence regarding the staging and risk assessment of pancreatic cancer with arterial invasion, possible treatment options and their technical details, and their effect on relevant outcomes. We present the following article in accordance with the Narrative Review reporting checklist (available at https://dx.doi.org/10.21037/cco- [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In another meta-analysis from 2020, 19 studies were included in an analysis involving 2,710 patients. Arterial resection was associated with a higher risk of death (RR: 4.09; P<0.001) and morbidity (RR: 1.4; P=0.01) and a shorter long-term survival (39). Also in 2020, Haines et al performed a metaanalysis of 13 studies with 467 patients who underwent pancreatic surgery with arterial resection for pancreatic cancer.…”
mentioning
confidence: 99%